Impact of the Age of Cecal Material Transfer Donors on Alzheimer’s Disease Pathology in 5xFAD Mice - Valeri, Francesco; dos Santos Guilherme, Malena; He, Fuqian; Stoye, Nicolai M.; Schwiertz, Andreas; Endres, Kristina (Microorganisms, 2021)
Alzheimer’s disease is a progressive neurodegenerative disorder affecting around 30 million patients worldwide. The predominant sporadic variant remains enigmatic as the underlying cause has still not been identified. Since efficient therapeutic treatments are still lacking, the microbiome and its manipulation have been considered as a new, innovative approach. 5xFAD Alzheimer’s disease model mice were subjected to one-time fecal material transfer after antibiotics-treatment using two types of inoculation: material derived from the caecum of age-matched (young) wild type mice or from middle aged, 1 year old (old) wild type mice. Mice were profiled after transfer for physiological parameters, microbiome, behavioral tasks, and amyloid deposition. A single time transfer of cecal material from the older donor group established an aged phenotype in the recipient animals as indicated by elevated cultivatable fecal Enterobacteriaceae and Lactobacillaceae representative bacteria, a decreased Firmicutes amount as assessed by qPCR, and by increased levels of serum LPS binding protein. While behavioral deficits were not accelerated, single brain regions (prefrontal cortex and dentate gyrus) showed higher plaque load after transfer of material from older animals. We could demonstrate that the age of the donor of cecal material might affect early pathological hallmarks of Alzheimer’s disease. This could be relevant when considering new microbiome-based therapies for this devastating disorder.